Hubungan Aktifitas Fisik dengan Derajat Dysmenorrhea Primer pada Remaja - Wati, Linda Ratna; Arifandi, Maya Devi; Prastiwi, Fatma (Journal of Issues in Midwifery, 2017)
ABSTRACTDysmenorrhea becomes on of the most common menstrual problems experienced by teenagers. Dysmenorrhea is divided into primary and secondary dysmenorrhea. Primary dysmenorrhea occurs without pelvic organ pathology. Physical Activity is one factor risk of primary dysmenorrhea. The aim of this study is to determine the association between physical activity with degree of primary dysmenorrhea in young women in The Undergraduate Midwifery Study Program of Medicine Faculty of Brawijaya University Malang. The design of this study is an observational analytical with prospective approach. The sample in this study amounted to 52 people selected by using purposive sampling. This study was conducted during two menstrual cycles. The test result by chi square analysis demonstrated an association between physical activity with the degree of primary dysmenorrhea with p value 0,000 (p <0,005). The conclusion from this study is a negative associated between physical activity with a degree of primary dysmenorrhea. As the result of this study there is suggestion that young women should be more concerned about their physical activity can reduce the pain felt at the time dysmenorrhea. The necessity of the role of health professionals to provide health education on primary dysmenorrhea so that the young woman concerned about their health.